Foreign direct investment, unionised labour markets and welfare - Cao, Jiyun; Mukherjee, Arijit (Elsevier, 2018)
Although empirical evidence on the relationship between labour union and foreign direct investment (FDI) is mixed, the theoretical literature mainly explains the negative relationship between labour union and FDI. We show that a multinational firm may prefer FDI in the presence of labour unions if it is sufficiently technologically superior to its domestic counterpart. FDI (compared to export) makes the domestic labour union better off but it makes the consumers, the domestic firm, the foreign labour union and the foreign country worse off, and may reduce domestic welfare. We show the implications of industry-wide and firm-specific labour unions.